PENCEGAHAN BULLYING KALANGAN REMAJA DI DESA NGIJO KECAMATAN KARANGPLOSO - Puspita Pebri Setiani; M. Iksan Gafa Wardana; Nur Anisa (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
Bullying is an act of using power to hurt a person or group of people verbally, physically, or psychologically so that the victim feels depressed, traumatized, and helpless. Teenagers who are victims of bullying are more at risk of health problems both physically and mentally. Bullying behavior often occurs if someone has a deficiency in him, both physically and mentally. Increasing the understanding of teenagers regarding bullying behavior can reduce cases of bullying, why prevention of bullying is very important from a young age because basically this bullying behavior is very dangerous. The impact of bullying for adolescents is in the form of mental disorders ranging from sensitivity, extreme anger, depression, low self-esteem, anxiety, decreased sleep quality, and feeling afraid to get along in a social environment. Through the bullying prevention counseling method, it is expected to have awareness and expertise in understanding the dangers of bullying behavior. The results of this activity are expected to be able to understand the dangers of bullying in an effort to prevent bullying behavior among teenagers.